Pengembangan aplikasi kesenian rengkong pada pembelajaran sastra berbasis kearifan lokal - Dinni Nurfajrin Ningsih; Aprilla Adawiyah; M.Irpan Abdurrohman Rozy (BAHASTRA, 2019)
The objective of this research was to describe the development of Rengkong art application and its utilization in the learning of literature based on local wisdom.  The research employed research and development method. This method was used to produce products and test the effectiveness of these products. Development of mobile-based learning media applications created using Android Studio software.  After the application creation process was complete, afterward the testing process and publishing to .apk format were carried out to make it available in the application market, namely the Google Play Store and could be operated on Android-based smartphones. Based on the results of the validation and implementation of the Rengkong application in learning, the following results were obtained: 1) The validation results of Rengkong application development in local wisdom-based literature learning fell into the category of sufficient to be used as learning material.  2) The results of the questionnaire of writing poetry learning towards the students of SMK Negeri 1 Cianjur with 33 respondents, obtained a percentage of 74%. It means that the use of Rengkong application in literature learning based on local wisdom could be used in learning because it was included in the sufficient category.  3) The values of character education in students' poems consist of: five values of appreciating achievement, two values of the love of the motherland, fourteen religious values, six values of honesty, three. values of hard work, six values of responsibility, four values of tolerance, and seven values of creativity